1993
DOI: 10.1021/j100148a033
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption calorimetric measurements and aluminum-27 DOR NMR studies on the molecular sieve aluminum phosphate-18

Abstract: Highly crystalline samples of the chabazite-related aluminophosphate AlPO4-18 (AEI) have been prepared and characterized by adsorption measurements as well as by *7Al double rotation (DOR) N M R studies. Whereas the heat curves and isotherms of n-paraffins on AEI show the common feature for adsorption on nonpolar molecular sieves with a given pore dimension, methanol gives an unusual heat curve with a deep minimum for a loading >4 molecules per cavity. This corresponds to the extended low-pressure hysteresis l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 2 publications
3
29
0
Order By: Relevance
“…The framework of aluminophosphate-type zeolites is built of AI0 4 and P04 tetrahedra in an alternating arrangement. The 27 Al DOR NMR spectra of these materials consist of narrow lines due to aluminum atoms on crystallographically inequivalent T -sites [259 -263] or caused by framework aluminum atoms interacting with probe molecules [264][265][266][267] . At the top of Fig.…”
Section: Ai Nmr Spedroscopy Of Framework and Non-framework Aluminumentioning
confidence: 99%
“…The framework of aluminophosphate-type zeolites is built of AI0 4 and P04 tetrahedra in an alternating arrangement. The 27 Al DOR NMR spectra of these materials consist of narrow lines due to aluminum atoms on crystallographically inequivalent T -sites [259 -263] or caused by framework aluminum atoms interacting with probe molecules [264][265][266][267] . At the top of Fig.…”
Section: Ai Nmr Spedroscopy Of Framework and Non-framework Aluminumentioning
confidence: 99%
“…This process satisfies the conditions necessary to time-average both first-and second-order perturbations to the Zeeman interaction which have spatial dependences described by the second-and fourth-order Legendre polynomials, P 2 (cos b) and P 4 (cos b), respectively [1,2]. A number of studies have been reported utilizing DOR NMR for the differentiation of sodium, boron, aluminium and oxygen sites in minerals [9][10][11], materials [12][13][14][15][16] and molecular sieves, including, zeolites [17][18][19][20], sodalites [21][22][23] and aluminophosphates [24][25][26][27][28]. Recently, focus has turned to exploiting DOR for the study of oxygen sites in organic solids [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…With water and other polar adsorbates, AIP04s exhibit hystereses extending to very low pressures, as illustrated with AlP04-5 in Fig. 2.5 [88,[92][93][94][95]. This sorption behavior of polar molecules in AlP04s is explained by coordinative adsorption of the polar molecule on specific framework aluminum sites.…”
Section: Adsorption Propertiesmentioning
confidence: 90%
“…Janchen et al suggested that the sorbate structure effectively interacting with the framework aluminum atoms and causing the phase transition is a methanol dimer [95]. Based on 27 Al DOR NMR, it could be shown that the Al atoms that adopt the Al v coordination in the as-synthesized material and after methanol adsorption are the same atoms [95]. Their position in the narrow part of the AEI cage is shown in Fig.…”
Section: Adsorption Propertiesmentioning
confidence: 99%